Identification of forest fire-prone region in Lamington National Park using GIS-based multicriteria technique: validation using field and Sentinel-2-based observations - Harikesh Singh; Sanjeev Kumar Srivastava (Geocarto International)
Lamington National Park in Queensland, Australia, is increasingly threatened by wildfires, intensified by climate change. This study integrates remote sensing, GIS, and the Analytical Hierarchy Process (AHP) to identify fire-prone areas within the park. Eight parameters were analyzed, with major fuel type being the most significant. Multispectral satellite data provided essential insights into landscape changes and vegetation stress, enhancing the understanding of wildfire risks. Historical records, field observations, and remote sensing data were utilized to develop and validate a Forest Fire Risk Index map, highlighting heightened fire susceptibility in the northern and eastern regions due to subtropical humid conditions. The findings emphasise the importance of advanced spatial analysis for proactive wildfire management. Combining remote sensing with GIS and multicriteria decision-making equips conservationists and policymakers with critical tools to strengthen wildfire response strategies, safeguard vital ecosystems, and protect surrounding communities. This approach is valuable for managing similar landscapes globally.